Special higher teacher education programs in Brazil: Questioning the transfer of teacher education programs to universities - isabel Melero Bello; Belmira Oliveira Bueno (Arizona State University, 2012)
The article focuses on in-service teacher education policies in Brazil and on actions developed since the 1990s by states and municipalities with a view to promote the higher education of primary school teachers. To such purpose, it analyzes the official discourses from that period, presents a map of special programs created to respond to such demands, and examines with the help of an ethnographic fieldwork a specific case and the practices through which the teachers appropriated the results of this program. The use of new formative devices, such as Distance Learning and TICs, and the involvement of new pedagogical agents, define the more visible aspects of this new formation model. Tensions between the micro and macro spheres of the policies adopted in this area could be sensed: on the one hand, the political success attending the graduation of thousands of teachers; on the other, pedagogical improvements still uncertain in view of the conditions under which the programs were conducted. This article questions the centralization and standardization promoted by these programs, the managerial logic presiding over its conception, the deflation of practice, and the small contribution of this kind of formation to the professionalization of the teaching activity.